Single versus repeated tramadol injection in laparotomized albino rats: comparison of effects on hematology, serum biochemical parameters, and body weight gain - Udegbunam, Rita Ijeoma; Okereke, Henry Nnamdi; Udegbunam, Sunday Ositadimma (Journal of Advanced Veterinary and Animal Research, 2015)
This study was aimed to assess the effects of single and repeated tramadol administration on some hematological and serum biochemical parameters of laparotomized rats. Laparotomized rats (n=18) were randomly divided into three equal groups. Normal saline was administered to the rats of group 1 (control). Tramadol (dosed at 10 mg/kg bwt) was administered singly to the rats of group 2. The same dose of tramadol was administered repeatedly every 12 h up to 72 h to the rats of group 3. On day 3 and 10 post-laparotomy (PSL), blood urea nitrogen, serum creatinine, total serum protein, hematocrit, hemoglobin concentration and red blood cell counts in the rats of group 2 were found to be significantly (P<0.05) higher than those obtained in group 1 and group 3. Mean weights of rats in group 1 and group 3 were significantly lower than those of the rats of group 2 PSL. This study showed that repeated tramadol administration lead to slower weight gain as well as marked decrease in biochemical and erythrocytic variables in rats. Therefore, single administration of tramadol PSL may suffice for analgesia. DOI: http://dx.doi.org/10.5455/javar.2015.b100